The Accuracy of Dynamic Parameters for Prediction of Fluid Responsiveness in Elderly Patients with Septic Shock - Paphawin S; Theerawit P; Junhasavasdikul D; Sutherasan Y (International Journal of General Medicine)
Sittikorn Paphawin,1,* Pongdhep Theerawit,2,* Detajin Junhasavasdikul,3 Yuda Sutherasan3 1Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Division of Critical Care Medicine, Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 3Division of Pulmonary and Pulmonary Critical Care Medicine, Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand*These authors contributed equally to this workCorrespondence: Yuda Sutherasan, Division of Pulmonary and Pulmonary Critical Care Medicine, Department of Medicine, Faculty of Medicine Ramathibodi Hospital, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +6622011619, Fax +6622011629 Ext 2, Email Sutherasan_yuda@yahoo.comPurpose: Assessed the accuracy of stroke volume variation (SVV), pulse pressure variation (PPV), and dynamic arterial elastance (Eadyn) in predicting fluid responsiveness (FR) and mean arterial pressure (MAP) response in elderly patients with septic shock.Patients and Methods: Mechanically ventilated patients aged over 65 with septic shock were enrolled. SVV, PPV, and Eadyn were recorded before and after FR testing (≥ 10% increase in cardiac output following a passive leg raise test or fluid challenge). MAP responsiveness was defined as a ≥ 10% increase in MAP post-fluid loading. Receiver operating characteristic curves were constructed to assess predictive parameters such as PPV, SVV for fluid responsiveness, and Eadyn for MAP response after loading. Optimal cutoff values were determined using the Youden index. Sensitivity, specificity, and area under the curve (AUC) were calculated. A p-value < 0.05 indicated statistical significance.Results: The mean age was 76 ± 8 years. Of the 104 patients, 46 were FR-positive. PPV and SVV were higher in FR-positive patients (PPV: 22.07 ± 11.02 vs 9.34 ± 7.39, p < 0.001; SVV: 20 ± 11 vs 9 ± 6, p < 0.001). The AUC was 0.875 for PPV, 95% confidence interval (CI) of 0.802– 0.947, and 0.841 for SVV, 95% CI of 0.757 − 0.925. Thresholds of 13.5% for PPV and 11.5% for SVV were found, with 81.8% sensitivity and 87% specificity. MAP responders had higher Eadyn (1.31 ± 0.54 vs 1.01 ± 0.93, p = 0.013). Eadyn showed an AUC of 0.844, with a threshold of 1.00 (sensitivity 85.7%, specificity 75%).Conclusion: PV, SVV, and Eadyn are predictors of FR and MAP responsiveness in elderly septic shock patients.Keywords: septic shock, elderly patients, pulse pressure variation, stroke volume variation, dynamic arterial elastance, fluid responsiveness